Comparative Analysis of Leadership and Economic Impact of the Palm Oil Industry in Indonesia - Mohd Huda, Mohd Ikbal (Business and Economic Research, 2024)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Palm oil is one of the biggest industries that contributed to Indonesia’s economy. In this context, this article aims to investigate a comparison of the government policies in Indonesia’s palm oil under the Jokowi leadership and the previous presidents and how this industry contributed to national economic growth. We reveal that every president has different programs to develop the palm oil industry. Soeharto Perusahaan Inti Rakyat (PIR) or Nucleus Estate and Smallholders (NES) program has greatly affected the extent of Indonesia’s large plantations today. Meanwhile, during Megawati’s presidency, there were not many changes in terms of policies or regulations. On the other side, under Susilo Bambang Yudhoyono’s presidency, Indonesia’s palm oil industry experienced new innovations in terms of palm oil policy. The biodiesel program that was introduced in 2006 made Indonesia’s palm oil industry move to the next stage. This policy aims to reduce Indonesia’s dependence on fossil fuels. Furthermore, this program became the forerunner of the biodiesel program which is currently being accelerated by President Jokowi. We argue that Jokowi’s programs such as the Biodiesel Mandatory Program (B30, etc.) through Pertamina, <em style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Peremajaan Sawit Rakyat, <span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Moratorium on land clearing permits, and cooperation through Council of Palm Oil Producing Countries (CPOPC) been the right step to stimulating the national economy.